Dengue Fever Outbreak in Delhi, North India: A Clinico-Epidemiological Study - Nishat Hussain Ahmed; Shobha Broor (Wolters Kluwer Medknow Publications, 2015)
Background: Dengue viruses, single-stranded positive polarity ribonucleic acid (RNA) viruses of the family Flaviviridae, are the most common cause of arboviral disease in the world. We report a clinico-epidemiological study of the dengue fever outbreak of 2010 from a tertiary care hospital in Delhi, North India. Objectives: Objectives of the study were to know the incidence of laboratory-confirmed dengue cases among the clinically suspected patients; to study the clinical profile of dengue-positive cases; and to co-relate the above with the prevalent serotype and environmental conditions. Materials and Methods: Four thousand three hundred and seventy serum samples from clinically suspected cases of dengue infection were subjected to μ-capture enzyme-linked immunosorbent assay (ELISA) for detection of dengue-virus-specific IgM antibodies. Virus isolation was done in 55 samples on C6/36 cell mono-layers. Clinical and demographic details of the patients were obtained from requisition forms of the patients or from treating clinicians. Results: Out of the 4,370 serum samples, 1,700 were positive for dengue-virus-specific IgM antibodies (38.9%). Prevalent serotype was dengue virus type-1. Thrombocytopenia and myalgia was seen in 23.1% and 18.3% of the 1,700 dengue IgM-positive patients, respectively. Also, 10.3% of 1,700 were dengue hemorrhagic fever (DHF) patients; and the mortality in serologically confirmed dengue fever cases was 0.06%. Conclusions: A change in the predominant circulating serotype, unprecedented rains, enormous infrastructure development, and increased reporting due to improved diagnostic facilities were the factors responsible for the unexpected number of dengue fever cases confronted in 2010.